2020
DOI: 10.1080/02813432.2020.1714143
|View full text |Cite
|
Sign up to set email alerts
|

How can task shifting put patient safety at risk? A qualitative study of experiences among general practitioners in Norway

Abstract: Objective: To describe experiences among general practitioners (GPs) in Norway regarding horizontal task shifting experiences associated with adverse events that potentially put patient safety at risk. Design and contributors: We conducted a qualitative study with data from a retrospective convenience sample of consecutive, already posted comments in a restricted Facebook group for GPs in Norway. The sample consisted of 43 unique posts from 38 contributors (23 women and 15 men), presenting thick and specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Although health care tasks might be redistributed to providers with less training to deliver cost savings or improve operational efficiencies, this purpose statement reinforces that TS/S occurs when health care redistribution and delegation is driven by efforts to enhance health equity by meeting the health needs of underserved populations [ 1 , 18 , 19 ]. The general purpose statement also asserts that TS/S achieves its goals without compromising the standards of care, including maintaining safety and quality [ 20 – 23 ]. Opportunities arising from TS/S programmes (Blue Box) The COATS Framework offers five opportunities for TS/S programmes to deliver health system improvements, depending on the implementation context.…”
Section: Resultsmentioning
confidence: 99%
“…Although health care tasks might be redistributed to providers with less training to deliver cost savings or improve operational efficiencies, this purpose statement reinforces that TS/S occurs when health care redistribution and delegation is driven by efforts to enhance health equity by meeting the health needs of underserved populations [ 1 , 18 , 19 ]. The general purpose statement also asserts that TS/S achieves its goals without compromising the standards of care, including maintaining safety and quality [ 20 – 23 ]. Opportunities arising from TS/S programmes (Blue Box) The COATS Framework offers five opportunities for TS/S programmes to deliver health system improvements, depending on the implementation context.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, five additional factors were suggested as unique for primary care and not included in in YCFF; timely access, primary-secondary interface, continuity of care, task performance (skill and competence) and enough time in the consultation [ 11 ]. Primary–secondary interface reflects our dimension Shared information and cooperation and the risk of horizontal task-shifting has been pointed out earlier [ 25 ]. Continuity of care reflects our dimension Risks in the environment/in the work conditions.…”
Section: Discussionmentioning
confidence: 99%
“…33 A study among GPs in 2018 showed the potential negative effects of task shifting from hospital specialists and other specialists to GPs on patient safety such as the hazardous delay of necessary examinations, or insufficient treatment due to lack of resources or risk of malpractice. 34 A study with data from 2018 documented long working weeks with a wide variety of tasks among GPs. 14 15 The evaluation study of 'The Regular General Practitioners Scheme' from 2019 35 confirmed significant growth in workloads for GPs during the last years that were related to increase both in new tasks and in the volume of established tasks.…”
Section: Open Accessmentioning
confidence: 99%